PENINGKATAN PEMAHAMAN KONSEP PADA MATERI INTERAKSI SOSIAL DAN LEMBAGA SOSIAL MELALUI METODE GIVING QUESTION AND GETTING ANSWER DI SMP IT NAJAAHAAN BOYONGBONG KELAS VII A - Resa Abdul Wazih; Lili Dianah; Sudarmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the improvement ofstudents’ conceptual understanding on socialinteraction and social institution materials through theGiving Question and Getting Answer (GQGA) methodin class VIIA of SMP IT Najaahaan Bayongbong, identify the implementation of the method in increasingstudents’ activeness and participation, examine theobstacles faced in implementing the method, andanalyze the teacher’s efforts to overcome theseobstacles. This research used a Classroom ActionResearch (CAR) method with a descriptive qualitativeapproach. Data collection techniques were carried outthrough observation, interviews, and documentation. The data were analyzed using the Miles andHuberman analysis technique, including data reduction, data display, and conclusion drawing. The results showed that the implementation of the GivingQuestion and Getting Answer method was able toimprove students’ conceptual understanding of socialinteraction and social institution materials. Studentsbecame more active in asking and answeringquestions, participating in discussions, and explainingthe material they had learned. In addition, this methodalso increased students’ confidence and participationduring the learning process. The obstacles found in implementing this method included students’ lack ofself-confidence, limited learning time, and differencesin students’ abilities in understanding the material. To overcome these obstacles, the teacher providedmotivation, additional guidance, formed study groups, and managed learning time more effectively. Based onthe results of the study, it can be concluded that theGiving Question and Getting Answer method iseffective in social studies learning to improve students’ conceptual understanding, activeness, andparticipation in class VIIA of SMP IT NajaahaanBayongbong.